Penerapan Teknologi Tepat Guna sebagai Strategi Pemertahanan Bahasa Jawa Serang dan Bebasan di Serang, Banten - Wulandari, Linda Sari; Rosalina, Erlyn (Sutasoma : Jurnal Sastra Jawa, 2021)
This study aims to analyze the defense of Serang Javanese and Bebasan Javanese, find language defense strategy that base on needs of the community in Domas Village, Pontang, Serang, Banten. The Serang Javanese dan the Bebasan Javanese need to be maintained regardless of current situation and condition, because languages ​​that still survive do not rule out the possibility of being threatened with extinction in future. This study uses a sociolinguistic with qualitative methods supported by quantitative methods. Data were collected through questionnaires and interviews. The results showed that the Serang Javanese still exists to be used by all ages in various spheres of life. However, the Bebasan Javanese is only used in the realm of certain speech partners. Based on the needs of the community, most people have MSMEs as their main source of income. However, MSMEs there have not been widely exposed to others community, so a non-transactional website is needed to market MSME products. MSME products can be promoted in the Serang Javanese language, the Bebasan Javanese Language, Bahasa and English. The website can become a solution in promoting MSME products as well as an effort to maintain the Serang Javanese and the Bebasan Javanese.